Nostalgia e memória em Andrei Tarkovski - Antonio Dante Rodrigues Acosta (2011)
The following study is developed considering fragments of the life course of Gorchakov, the foreign character of Andrei Tarkovski's movie Nostalgia (1983). Such fragments allowed me to draw up short journeys adressing time and memory, closely followed by Frances Yates' wording on the Art of Memory, as well as the writings of Tarkovsky himself about the Sculpting in Time. This dissertation is, above anything else, the result of a deep admiration for the film work of this Russian artist, as well as for his poetry about faith in the transformation of the man. This admiration derives a large portion of my rapture in relation to Tarkovsky's images, and in the way these act in my mind as a force of inspiration.